Hydro-Oceanographic Conditions in the Development of Tinobu Port Lasolo Sub-district North Konawe Regency Southeast Sulawesi Province - Chaerul, Muhammad; Usman, Rizki (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Indonesia is one of the world's largest maritime countries, with many small islands scattered from Sabang to Merauke. Therefore, the presence of a port plays a crucial role in maritime transportation, which is highly essential for the Indonesian population. When planning a port, there are numerous aspects to consider, ranging from environmental to structural aspects of the port's development. In this context, researchers conducted a study to analyze the water conditions around Tinobu Port, specifically focusing on topography, bathymetry, and tides, often referred to as Hydro-Oceanography. These three aspects of Hydro-Oceanography play a vital role in port planning, as topography and bathymetry shape the land and water contours, and tidal analysis determines elevation bindings.